Teenagers' mental health problems predict probable mental diagnosis 3 years later among girls, but what about the boys? - Carlén Kristina; Suominen Sakari; Augustine Lilly; Saarinen Maiju M.; Aromaa Minna; Rautava Päivi; Sourander André; Sillanpää Matti (BMC, 2025)
Background
The prevalence of mental disorders is increasing, and there seems to be a gender difference in prevalence, with girls reporting more mental health problems than boys, especially regarding internalizing problems. Most mental disorders debut early but often remain untreated into adulthood. Early detection of mental disorders is essential for successful treatment, which is not always happening. The study aimed to estimate to what extent teenagers' self-reports predict probable mental diagnosis as they enter adulthood, particularly regarding gender differences.
Methods
Self-reported mental health problems, Youth Self-Report (YSR) at 15 years (range 3-110, n = 504) from the ongoing Finnish family competence study (FFC) using modified multivariable Poisson regression analysis for prediction of DAWBA (Development and Wellbeing Assessment) interview outcomes 3 years later.
Results
One unit's increase in YSR was estimated to correspond to an increase in the relative risk of a probable DAWBA-based diagnosis by 3.3% [RR (95% CI) 1.03 (1.03-1.04), p < 0.001]. In gender-specific analysis, the findings applied, particularly to girls.
Conclusions
Youth Self-Report (YSR) scores at pubertal age predicted the risk of a probable mental diagnosis at the onset of adulthood, particularly in girls. Further research is needed to explain the lower sensitivity of YSR among boys.